Pengalihan Hak Atas Tagihan Atas Nama atau Cessie yang Berkepastian Hukum - Lemta , Benjamin; Iryani, Dewi; Aji , Puguh (Advokasi Hukum & Demokrasi (AHD), 2024)
Debt and credit transactions are common occurrences in business activities. Often, debtors are unable or have not yet fulfilled their obligations, while creditors need immediate funds even before the due date of their receivables. In such cases, Civil Law provides a solution through the institution of "cessie," which is the Transfer of Rights to a Claim. However, the legislation governing cessie is still limited, as it is only addressed in Article 613 of the Civil Code (KUHPerdata), and even that does not comprehensively regulate the matter, leading to disputes that may escalate to court. Article 613 of the Civil Code lacks sufficient provisions for the implementation of cessie, as it only states that the transfer of cessie must be done through an authentic deed or a private document and will only be legally effective against the debtor if it has been notified to them. However, it does not specify who should make the notification, when it should be made, and how it should be done, resulting in legal uncertainty. This research adopts the Juridical Normative method, utilizing two approaches: the Statute Approach, which examines all relevant laws, and the Conceptual Approach, which involves studying legal doctrines and opinions from experts in law. The Transfer of Rights to a Claim (Cessie) transaction has not provided legal certainty for all parties involved, including the cessus (debtor), cedent (transferor), and cessionaris (transferee). This is evident from court decisions in various cases that show inconsistency in how notification is made to cessus. Whether of whether notification is sufficient when done by the cedent or the cessionaris, whether through regular mail or the Court Bailiff's writ, remains unsettled.